Perubahan Budaya Bermukim Masyarakat Riparian Sungai Musi Palembang, Tinjauan Proses dan Produk - Bambang Wicaksono (Jurnal Tekno Global, 2019)
AbstractOne embodiment of the ethnic culture is the life of the river side, in which there are constituent building elements and local wisdom. Settlements can be categorized as vernacular architectural works in the sense that they are designed, built and used. The water space that was previously so vast, now began to narrow down with the presence of land space. The river experienced a narrowing and even hoarding in several places, which caused a decline in the function of the river for its people. Stage houses or rafts that used to respond to the river now turn to non stage (characterized by land houses). This has the potential to cause loss of local potential and local architectural identity. This study aims to determine the cultural changes living in the riparian community of the Musi Palembang river. In achieving this goal, a study was conducted to identify the architectural footprint, explore activities and ideas of the riparian community of Sumgai Musi. Data collection was carried out through field observations, in-depth interviews, and literature studies. Analysis was carried out qualitatively on variables, process characteristics and products from identification of riverbank settlements. The results with based on the process and product, showed that most of the riverside houses experienced physical changes in the building, both from the function and building materials. Then with the decline of the existence of the river, the community made a new road network and more land land. The study concluded that the cultural change living on the banks of the river was caused by the loss of identity of the riparian settlement of the Musi river.Keywords : Change, Settlement, Riparian, River, Vernacular AbstrakSalah satu perwujudan dari budaya suku bangsa adalah kehidupan bermukim tepi sungai, yang di dalamnya terdapat elemen bangunan penyusunnya serta kearifan. Permukiman dapat dikategorikan sebagai karya arsitektur vernakular yang dalam pengertian didesain, di bangun dan digunakan. Ruang air yang sebelumnya demikian luas, sekarang mulai dipersempit dengan kehadiran ruang daratan. Sungai mengalami penyempitan bahkan penimbunan di beberapa tempat, yang menyebabkan penurunan fungsi sungai bagi masyarakatnya. Rumah-rumah panggung atau rakit yang dahulunya merespon sungai sekarang beralih ke non panggung yang bercirikan rumah darat. Hal ini berpotensi menyebabkan hilangnya potensi lokal dan identitas arsitektur lokal. Penelitian ini bertujuan untuk mengetahui perubahan budaya bermukim masyarakat riparian sungai Musi Palembang. Dalam mencapai tujuan tersebut, dilakukan studi untuk mengidentifikasi jejak arsitektur, mengekplorasi aktivitas dan gagasan masyarakat riparian sungai Musi. Pengumpulan data dilakukan melalui observasi lapangan, wawancara mendalam, dan studi pustaka. Analisis dilakukan secara kualitatif terhadap variabel, karakteristik proses dan produk dari identifikasi permukiman tepi sungai. Berdasarkan hasil tinjauan proses dan produk, menunjukkan bahwa sebagian besar rumah tepian sungai mengalami perubahan fisik bangunan, baik dari fungsi maupun material bangunan. Kemudian dengan menurunnya eksistensi sungai membuat masyarakat membuat jaringan jalan baru dan lebih bepola darat. Studi menyimpulkan bahwa perubahan budaya bermukim tepian sungai disebabkan oleh hilangnya identitas permukiman riparian sungai Musi. Kata kunci: Perubahan, Permukiman, Proses-Produk, Riparian, Sungai, Vernakular